ANALISIS TINGKAT KESEHATAN PT. BANK SULUT, TBK DENGAN MENGGUNAKAN RASIO KEUANGAN - Palar, Dewi Syane; Pelleng, Frendly; Manoppo, Wilfred (Sam Ratulangi University, 2015)
Absract. This study aims to determine the financial health of Bank of North Sulawesi. Research using quantitative descriptive analysis, by measuring financial ratios through a comparison of the financial statement items with more posts that have relevant relationships by using analysis of three financial ratios, namely Liquidity, Solvency and Profitability. The data used are the financial statements of the year 2011 until the year 2013. The results showed levels of liquidity, solvency and profitability of PT Bank of North Sulawesi experienced fluktuatuf. Although financial statement has fluctuated, but the financial soundness of PT. Bank of North Sulawesi relatively healthy because they are on the standards set by Bank Indonesia. Keywords: Financial Ratios, Financial Health